2015
DOI: 10.1186/s40792-015-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic radical esophagectomy and laparoscopic transhiatal lymph node dissection for superficial esophageal cancer associated with lymph node metastases in the dorsal area of the thoracic aorta

Abstract: Esophageal cancer invading the muscularis mucosa sometimes involves regional lymph node metastases. However, lymph node metastases are rare in the dorsal area of the thoracic aorta. We describe a patient with an intramucosal esophageal cancer invading the muscularis mucosa, accompanied by lymph node metastases in the dorsal area of the thoracic aorta. These lesions were successfully resected by hand-assisted laparoscopic surgery using a transhiatal approach. A 60-year-old man was diagnosed with superficial eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Past reports have demonstrated several approaches for dissecting posterior TPAN: the left thoracotomy approach, the left thoracoscopic approach, and the transhiatal approach [3][4][5][6][7]. Although the transhiatal approach is less invasive, the narrow surgical space increases the manipulation complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past reports have demonstrated several approaches for dissecting posterior TPAN: the left thoracotomy approach, the left thoracoscopic approach, and the transhiatal approach [3][4][5][6][7]. Although the transhiatal approach is less invasive, the narrow surgical space increases the manipulation complexity.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the patients with posterior TPAN metastasis had more advanced cN and cM stages than those with anterior TPAN, suggesting that posterior TPAN is a systemic disease. However, several case reports have shown that complete dissection improved the prognosis of patients with cStage IVB esophageal cancer who presented with solitary posterior TPAN metastasis [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Shiozaki et al reported that the posterior mediastinal lymph nodes, including those around the anterior area of thoracic aorta, could be dissected using the pneumomediastinum method [11] . Ninomiya et al reported on dissection of lymph nodes in the DTA performed using transhiatal mediastinoscopy [12] . During the pneumomediastinal procedure, the operating field is deep and narrow, and the mediastinoscopic view would be more limited with this procedure than with the thoracoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastasis is among the most crucial negative prognostic factors affecting cancer patients[ 6 ]. Thoracic para-aortic lymph node (TPLN) metastasis, a rare complication of esophageal cancer, has only been described in a few case reports[ 7 , 8 ], although in one case report, it was observed that there was a higher incidence of metastasis with recurrent disease[ 9 ]. Generally, two-field lymphadenectomy is commonly performed in Western countries and China[ 3 - 5 ], whereas extended three-field lymphadenectomy is performed in Japan[ 10 ].…”
Section: Introductionmentioning
confidence: 99%